Building with Time, History, and Resilience at Yale. Issue 1 (12th June 2019) - Trachtenberg, Marvin
Abstract : This article examines Louis Kahn's design for the New Yale Art Gallery as an exemplar of 'building-in-time.' The novel design breaks formally with then modernist-free architecture of the Yale campus, and yet complements and completes the existing structures of the art gallery, to which it acted as an addition. Kahn's genius lay in his ability to find a solution within the problem itself — within the older buildings — in effect 'rediscovering' and bringing to bear 'lost' methods of building-in-time. He also might be said to have activated the properties of resilience latent in the existing art gallery.